2021
DOI: 10.1002/mds.28490
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of LRRK2 in Parkinson's Disease Patient Blood by a G2019S Selective LRRK2 Inhibitor

Abstract: A BS TRACT: Background: A common genetic mutation that causes Parkinson's disease (PD) is the G2019S LRRK2 mutation. A precision medicine approach that selectively blocks only excess kinase activity of the mutant allele could yield a safe and effective treatment for G2019S LRRK2 PD. Objective: To determine the activity of a G2019S mutant selective leucine-rich repeat kinase 2 (LRRK2) kinase inhibitor as compared to a nonselective inhibitor in blood of subjects with genetic and idiopathic PD on two LRRK2 biomar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Furthermore, we identified 11 additional candidate LRRK2 variants that may contribute to IBD-PD comorbidity. Previous studies have already reported L119P, S1228T, R1628P, M1646T, and Y2189C as PD risk variants [ 66 69 ], while I1371V has been shown to cause increased phosphorylation and aggregation of α-synuclein in neurons [ 70 ]. Additionally, P1542S is a common variant (gnomAD MAF = 0.03) and has been listed as a CD-associated polymorphism in HGMD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified 11 additional candidate LRRK2 variants that may contribute to IBD-PD comorbidity. Previous studies have already reported L119P, S1228T, R1628P, M1646T, and Y2189C as PD risk variants [ 66 69 ], while I1371V has been shown to cause increased phosphorylation and aggregation of α-synuclein in neurons [ 70 ]. Additionally, P1542S is a common variant (gnomAD MAF = 0.03) and has been listed as a CD-associated polymorphism in HGMD [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the authors themselves rightly observe, this "is remarkable, given that G2019S-LRRK2 differs from WT-LRRK2 only by a single amino acid" (Garofalo et al, 2020). Unfortunately, this molecule is unlikely to be developed further as it is unable to cross the blood-brain barrier, but we note that another G2019S-selective indazole compound identified in the same work has since been shown to inhibit LRRK2 kinase activity in peripheral blood mononuclear cells (PBMCs) from homozygous G2019S LRRK2 patients, but not in cells from wild-type controls (Bright et al, 2021). Thus, even though these molecules may only be suitable for G2019S LRRK2 PD patients, there is clearly a lot of potential in this project and we await further developments.…”
Section: Atp-competitive Lrrk2 Kinase Inhibitorsmentioning
confidence: 91%
“…A total of 2 LRRK2 kinase inhibitors, DNL201 (NCT03710707) and DNL151 (NCT04056689), will soon enter late‐stage clinical trials, with DNL151 being advanced first (Denali Therapeutics, South San Francisco, CA). There are other inhibitors in preclinical phases and include MLi‐2, PF‐06685360, 24 and EB‐42168, a selective kinase inhibitor that may avoid the peripheral toxic effects of the nonselective inhibitors 25 . The second approach is antisense oligonucleotides (ASOs) to reduce LRRK2 mRNA transmission.…”
Section: Gene‐targeted Therapiesmentioning
confidence: 99%
“…There are other inhibitors in preclinical phases and include MLi‐2, PF‐06685360, 24 and EB‐42168, a selective kinase inhibitor that may avoid the peripheral toxic effects of the nonselective inhibitors. 25 The second approach is antisense oligonucleotides (ASOs) to reduce LRRK2 mRNA transmission. A mouse PD model 26 demonstrated that LRRK2 ASOs injected into the brain reduce LRRK2 protein levels and the formation of α‐synuclein inclusions.…”
Section: Gene‐targeted Therapiesmentioning
confidence: 99%